Notes on some newly recorded fish from Andhra Pradesh coast, India - Joseph Stanley Yogesh Kumar; Arya Sen; Chelladurai Raghunathan (Journal of Fisheries, 2024)
Eleven fish species, namely Heniochus singularius Smith & Radcliffe, 1911; Entomacrodus vermiculatus (Valenciennes, 1836); Pomacentrus similis Allen, 1991; Myripristis berndti Jordan & Evermann, 1903; Myripristis seychellensis Cuvier, 1829; Sargocentron cornutum (Bleeker, 1854); Thalassoma lunare (Linnaeus, 1758); Pardachirus pavoninus (Lacepède, 1802); Paraplotosus albilabris (Valenciennes, 1840); Canthigaster papua (Bleeker, 1848), have been documented for the first time in Andhra Pradesh state of India associated with artificial reef and rocky shoreline habitats. Additionally, E. thalassinus has been recorded for the first time in India from this study. The study provides detailed descriptions of the diagnostic characteristics and distribution of these ten species. These findings highlight the richness of fish fauna along the Andhra Pradesh coastline of India.